ANALISIS PENDAPATAN DAN KELAYAKAN USAHA INDUSTRI MINYAK NILAM DI DESA LUMBUTAROMBO KECAMATAN BANAWA SELATAN KABUPATEN DONGGALA - Taha, Anggriyani Ridwan; Alam, Max Nur (AGROTEKBIS, 2016)
This study aims to determine the feasibility and income on Patchouli Oil Industry at the Village Lumbutarombo Donggala District of South Banawa. This research was conducted in the village of Lumbutarombo in September 2015. The determination of the respondents in this research was intentionally (purposive), selected respondents were higher rank staff and employees of Patchouli Oil Industry. The data used in this study derived from primary data and secondary data. The analysis was done for income and feasibility of this industry. The results showed that income per month patchouli oil industry was 15,950,375 IDR and the Patchouli Industry is feasible with 1.18 as R/C value.Key Words: Feasibility, Income, and Patchouli Oil Industry.